Corynecercospora- a hitherto undescribed hyphomycetous genus - and D.K. AGARWAL, VIVEK KUMAR PAL, MASOOD AKHTAR, NASIM AHMAD, KAMAL* (Indian Phytopathology, 2006)
A new taxon Corynecercospora teraiensis gen. et sp. nov. occurring in white powdery form on the living leaves of Elaeodendron glaucum L. was recorded. The ectotrophic hyphomycetous fungus producing vegetative appendages with hyphopodia, macronematous conidiophores, acropleurogenous conidiogenous cells and enteroblastic tretic, distoseptate conidia. The new taxon has been described, based on comparison with the allied forms, which do not match with any of the anamorphic forms described so far.